Urban Development in Longyearbyen: Dealing with Local Challenges in a Town that Serves as a Tool for Svalbard Policies - Meyer, Alexandra (Zenodo, 2022)
Abstract Svalbard’s main urban centre, Longyearbyen, is a town in constant transition. Established as a coal mining camp, it developed into a mono-industrial company town, was then transformed into a “normal” Norwegian family town, and is today profoundly impacted by climate change and undergoing economic, social and cultural changes at high speed. In this chapter, I examine urban planning and development in Longyearbyen, looking at historical developments and discussing current challenges. I trace the development of the town and show how the societal transformations beginning in the 1970s led to an institutionalization and formalization of urban planning. I then discuss three main issues and challenges related to community development today, brought about by rapid climate and socio-economic change: securing the town against environmental changes, the housing crisis, and a changing identity. I argue that throughout its history, Longyearbyen’s function for the Norwegian state as an upholder of presence and legitimation of sovereignty over the Svalbard archipelago has set the premises of urban development and planning. This makes for a complex planning context, in some cases limiting local control and participation. The chapter draws on existing literature, policy and planning documents, as well as ethnographic fieldwork in Longyearbyen.